Evaluation of the effects of different file systems and apical functions of integrated endodontic motors on debris extrusion: an ex vivo experimental study - Sıla Nur Usta; Antonio Magan-Fernandez; Cumhur Aydın (Restorative Dentistry & Endodontics)
Objectives This study aimed to evaluate the effects of two different file systems operated with three apical functions of an endodontic motor integrated with an electronic apex locator on debris extrusion. Methods Sixty single-rooted teeth were prepared and divided into two main groups and three subgroups based on the file system (OneShape [Micro-Mega SA] and WaveOne [Dentsply Maillefer]) and apical function of the endodontic motor used (auto apical stop [AAS], auto apical reverse [AAR], and auto apical slowdown [ASD]). The teeth were mounted in pre-weighed glass tubes filled with 0.9% sodium chloride to complete the circuit with the apex locator. Files were advanced until the respective apical function (stop, reverse, or slowdown) was activated. The extruded debris was collected, dried, and weighed by subtracting pre-weighed values from post-weighed values. Preparation time was also recorded. Statistical analyses were performed to compare the groups. Results OneShape was associated with significantly less debris extrusion compared to WaveOne, regardless of the apical function (p < 0.05). The ASD function resulted in the least debris extrusion compared to AAS and AAR (p < 0.05). Preparation time was significantly longer in the ASD function (p < 0.05), while no differences were observed between the file systems (p > 0.05). Conclusions The OneShape file system and the ASD function produced the least amount of apical debris. While the ASD function requires more preparation time, its potential to minimize debris extrusion suggests it may reduce postoperative symptoms.